2021
DOI: 10.3390/bioengineering8070099
|View full text |Cite
|
Sign up to set email alerts
|

Genitourinary Tissue Engineering: Reconstruction and Research Models

Abstract: Tissue engineering is an emerging field of research that initially aimed to produce 3D tissues to bypass the lack of adequate tissues for the repair or replacement of deficient organs. The basis of tissue engineering protocols is to create scaffolds, which can have a synthetic or natural origin, seeded or not with cells. At the same time, more and more studies have indicated the low clinic translation rate of research realised using standard cell culture conditions, i.e., cells on plastic surfaces or using ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 221 publications
0
22
0
Order By: Relevance
“…Adhesion, proliferation, and metabolism of nine fibroblast populations from three different organs were evaluated in 2D cell cultures. Fibroblasts from the skin, bladder, and vagina were chosen because the reconstruction of substitutes of these source organs using the self-assembly method that has been published [ 22 , 24 , 25 , 26 ]. The diversity of primary fibroblast populations in terms of organ type, anatomical sites, sex, and age constitutes one of the limitations of this article.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adhesion, proliferation, and metabolism of nine fibroblast populations from three different organs were evaluated in 2D cell cultures. Fibroblasts from the skin, bladder, and vagina were chosen because the reconstruction of substitutes of these source organs using the self-assembly method that has been published [ 22 , 24 , 25 , 26 ]. The diversity of primary fibroblast populations in terms of organ type, anatomical sites, sex, and age constitutes one of the limitations of this article.…”
Section: Discussionmentioning
confidence: 99%
“…It can be expected that the tissues reconstructed by this technique recreate more faithfully the interactions between cells and the extracellular matrix (ECM) and those between cells themselves compared to what can be obtained using the other tissue engineering models. The scope of this approach grew over time to allow the production of effective tissues for organ transplantation [ 20 ] and as models for fundamental studies [ 2 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…While these replacements may be reasonably successful in a majority of cases, there is still a substantial risk of graft failure arising from myriad complications, not to mention associated donor-site morbidity. 193,194 Efforts to engineer natural or artificial scaffolds for urinary tract repair have yielded some promising early results. The seminal work of Atala and colleagues showed that an artificial scaffold composed of PGA and collagen and pre-seeded with autologous urothelial and SMCs can improve bladder function.…”
Section: Urinary Tractmentioning
confidence: 99%
“…to produce mature tissue organization. 194,206 Two issues common in urethral repair using biomaterial scaffolds have been mechanical mismatch and lack of neovascularization.…”
Section: Urethramentioning
confidence: 99%
“…While some successes using MSC in vivo for tissue engineering based repair of cartilage defects in humans [13,14] and pig models [15,16] have been noted, there have also been a number of endeavors for other applications such as for genitourinary tissues [17,18] and solid organs [19] that have been more challenging, but progress is being made. Thus, the myriad of studies and significant effort to develop the perceived stem cell potential of adult MSC has been very challenging, but some successes have been noted with in vitro tissue engineered constructs in contrast to more limited successes following injection of free cells either systemically or into a localized site.…”
Section: Introductionmentioning
confidence: 99%